A Need for Evidence-Based Answers to Coagulation and Pharmacogenetics - Shuman, Jill (MD Conference Express, 2015)
The role of global coagulation assays in the clinical setting is unclear. Clinical trials are needed to further assess the relationship between global assays and clinical bleeding. Despite the promise of pharmacogenetics, evidence-based trials are needed to clarify the association between genotype and clinical outcomes, especially related to warfarin.